2019
DOI: 10.2147/idr.s211618
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular Detection Of Multidrug-Resistant <em>Salmonella</em> Isolated From Livestock Production Systems In South Africa</p>

Abstract: Background: Antibiotic-resistant bacterial pathogens associated with livestock remain a major concern worldwide as they get transmitted from animals to humans and cause foodborne and zoonotic diseases. Methods: Antimicrobial resistance in livestock-associated Salmonella spp in South Africa was investigated using molecular DNA methods. Three hundred and sixty-one environmental faecal samples were randomly collected from avian (chicken and ducks), cows, pigs, goats, and sheep. Salmonella spp. were isolated on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 76 publications
(96 reference statements)
3
31
3
Order By: Relevance
“…The present study represented that, 100% of the mcr-1 positive isolates were MDR. Similar findings were reported on MDR in Salmonella isolates from Bangladesh and different parts of the world (29, 6772). Due to the indiscriminate victimization of antimicrobial agents, MDR strains may apparently be occurred with high incidence in this area which is a serious concern for veterinary medicine and also for human health since direct transmission of resistant isolates from animals to humans has been confirmed (73).…”
Section: Discussionsupporting
confidence: 88%
“…The present study represented that, 100% of the mcr-1 positive isolates were MDR. Similar findings were reported on MDR in Salmonella isolates from Bangladesh and different parts of the world (29, 6772). Due to the indiscriminate victimization of antimicrobial agents, MDR strains may apparently be occurred with high incidence in this area which is a serious concern for veterinary medicine and also for human health since direct transmission of resistant isolates from animals to humans has been confirmed (73).…”
Section: Discussionsupporting
confidence: 88%
“…Equally of potential therapeutic importance was the detection of a very high (94.0%) prevalence of MDR isolates of Salmonella. Other studies of the pathogens of poultry in South Africa have similarly reported a high prevalence of MDR in Salmonella isolates in chickens and other livestock, thus highlighting their therapeutic and public health implications [ 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The prevalence of MDR in the current study is higher than was reported, also using the disc diffusion method, for Salmonella from chickens (caeca) in Trinidad, 14.3% [ 46 ], Portugal, 75.0% [ 57 ], China, 80.0% [ 58 ], and in the USA, 92.0% [ 59 ], but lower than that reported for isolates in Nepal, 100% [ 60 ], Mauritius, 100% [ 61 ] and Trinidad, 100.0% [ 41 ] and globally [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These production systems have been linked to the occurrence of several zoonotic and non-zoonotic outbreaks worldwide ( 11 , 14 , 15 , 64 ). BPS maintain a wide spectrum of species that harbor STEC, including cattle ( 22 ), sheep and goats ( 23 , 65 ), and poultry and captive wild birds ( 11 , 24 ). Positivity reported by this study (11.76%) is similar to what has been reported in productive animal species (cattle and swine) under industrialized conditions in Chile ( 7 ).…”
Section: Discussionmentioning
confidence: 99%